Metode llmiah Ulama Klasik - Miftakhul Anwar (Institut Agama Islam Sahid (INAIS) Bogor, 2020)
The scientific method is a way or steps to implement a work plan that has been prepared so that the goals set can be achieved systematically, empirically and in a controlled manner. The principles of the western scientific method are formulating problems, formulating hypotheses, collecting data, testing hypotheses and formulating conclusions based on ratios and empirical without involving revelation. The principles of the Islamic scientific method are formulating problems, formulating hypotheses, collecting data, testing hypotheses and formulating conclusions based on the revelations of the Qur'an, al-Hadith or direct guidance given, rational and empirical. The scientific method of the hadith scholar, namely Imam Bukhari, sets high standards in the selection of hadiths so that the hadiths collected in his work are the most authentic hadiths and can be accounted for. The scientific method of the scholar of science, namely Jabir Bin Hayyan, with the experimental method he created himself, by mastering theories before conducting experiments or experiments so that the results of the experiments carried out are minimal errors that cause harm and harm